The Management of Infection and Colonization due to Methicillin-Resistant Staphylococcus aureus: A CIDS/CAMM Position Paper - Andrew E Simor; Mark Loeb; the CIDS/CAMM Guidelines Committee (Canadian Journal of Infectious Diseases)
Methicillin-resistant Staphylococcus aureus (MRSA) is being seen with greater frequency in most hospitals and other health care facilities across Canada. The organism may cause life-threatening infections and has been associated with institutional outbreaks. Several studies have confirmed that MRSA infection is associated with increased morbidity and mortality compared with infections caused by susceptible strains, even when the presence of comorbidities is accounted for. Treatment of MRSA infection is complicated by the fact that these organisms are resistant to multiple antimicrobial agents, so treatment options are limited. The effectiveness of decolonization therapy (attempting to eradicate MRSA carriage) is also uncertain. This paper reviews the medical management of MRSA infections, discusses the potential role of decolonization and provides an overview of evidence to support recommended infection control practices.